CRANIOSYNOSTOSIS – PATHOGENESIS, CLASSIFICATION AND CLINICAL CONSEQUENCES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Craniosynostosis is a congenital disorder characterized by the premature fusion of one or more cranial sutures, resulting in abnormal skull growth and potential impairment of brain development. The condition may occur as an isolated anomaly or as part of a genetic syndrome. Early diagnosis and optimal management are crucial to prevent increased intracranial pressure, neurodevelopmental delay, and aesthetic deformities. This article reviews the epidemiology, pathogenesis, classification, clinical manifestations, and potential complications of craniosynostosis.